Suicide attempt in Armenia 2016-2018 description (Revista de Investigaciones Universidad del Quindío, 2020)
Introduction: The national incidence rate of the suicide attempts has grown year after year, where the department of Quindío is above the countries’ rate, making it mandatory to have a characterization of the population as well as the identification of the factors related to the attempt of suicide in the region.Objective: Describe the attempt of suicide in the city of Armenia (Quindío) between 2016 and 2018.Methodology: A descriptive observational study was conducted with a first suicide attempted reported by SIVIGILA using descriptive statistics, Chi square tests and Mann Whitney.Results: A sample of 598 reported suicide attempted cases was analyzed, where more of the 50% were people under 29 years old, and according to their marital status, 68.9% did not have a partner at the moment, the predominant socioeconomic stratum was low and the most frequent mechanism was poisoning. There was a finding in the relation between previous suicide attempts and legal problems, psychiatric disorder backgrounds and consumption of psychoactive substances (SPA). According to the epidemiological period in the years analyzed, the tendency was increasing for the IX and XI periods.
Keywords: Suicide; suicide attempted; suicidal Ideation; risk factors; Precipitating Factor; MeSH